2009
DOI: 10.1213/ane.0b013e3181b31f39
|View full text |Cite
|
Sign up to set email alerts
|

Complete Freund’s Adjuvant-Induced Intervertebral Discitis as an Animal Model for Discogenic Low Back Pain

Abstract: Intradiscal CFA injection led to chronic disk degeneration with allodynia, which was suggested by pain behavior and expression of pain-related mediators. The increment of CGRP, PGE, and iNOS also suggest pain-related signal processing between the IVD and the neural pathway in this animal model. This animal model may be useful for future research related to the pathophysiology and development of novel treatment for spine-related pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…These findings suggested that the disc inflammatory state might play a more important role in the level of pain. The association between pro-inflammatory cytokines and discogenic pain was previously demonstrated using an intradiscal injection of complete Freund adjucant, a pro-inflammation mediator, to induce discitis [18]. However, this is the first study to investigate the association between TNFα, a natural pro-inflammatory cytokine thought to be an initiator of disc degeneration, and painful behavior in vivo.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These findings suggested that the disc inflammatory state might play a more important role in the level of pain. The association between pro-inflammatory cytokines and discogenic pain was previously demonstrated using an intradiscal injection of complete Freund adjucant, a pro-inflammation mediator, to induce discitis [18]. However, this is the first study to investigate the association between TNFα, a natural pro-inflammatory cytokine thought to be an initiator of disc degeneration, and painful behavior in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…Hindpaw mechanical hyperalgesia is a measurement of pain sensitivity using a series of calibrated von Frey filaments corresponding to forces between 0.4 and 26.0 g (Stoelting, Wood Dale, IL, USA) [18,19]. After 20 minutes acclimations, calibrated filaments were applied in ascending order from 0.4 g to 26.0 g until a positive response was elicited.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significantly decreased pain threshold—as measured by vocal responses to microfilaments applied to the spinous process—was found up to 7 weeks after puncturing the L5/6 IVD ventrolaterally with a 26-gauge needle and injection of 10 μL complete Freund’s adjuvant (CFA) with an anterior approach in a rat. 108 Our group has developed a model of painful IVD degeneration wherein an anterior IVD puncture with TNF-α injection induces a decreased mechanical hindpaw withdrawal threshold. 44 We believe the use of TNF-α is more physiologically relevant than CFA, as TNF-α has been extensively implicated in IVD degeneration and may better lend itself to understanding the underlying pathophysiology of IVD degeneration–related pain in an animal model.…”
Section: Existing Models Of Painful Ivd Degenerationmentioning
confidence: 99%
“…The ingrowth of nociceptive neural fiber into deeper parts of the degenerative disc is considered as one of the most widely accepted pathomechanisms related to chronic discogenic pain (87). As the IVDD proceeds, disc inflammation may promote axonal growth of afferent fibers from the dorsal root ganglia (DRG) (88) to innervate the disc by secreting proinflammatory mediators.…”
Section: Applications Of C60 and Derivatives In Orthopaedic Researchmentioning
confidence: 99%